Celecoxib Adjunctive Treatment to Antipsychotics in Schizophrenia: A Review of Randomized Clinical Add-On Trials - Stefano Marini; Domenico De Berardis; Federica Vellante; Rita Santacroce; Laura Orsolini; Alessandro Valchera; Gabriella Girinelli; Alessandro Carano; Michele Fornaro; Francesco Gambi; Giovanni Martinotti; Massimo Di Giannantonio (Hindawi Limited, 2016)
Schizophrenia is a severe, chronic and debilitating mental disorder. Past literature has reported various hypotheses about the psychopathology of schizophrenia. Recently, a growing literature has been trying to explain the role of inflammation in the etiopathogenesis of schizophrenia. In the past, numerous immune modulation and anti-inflammatory treatment options have been proposed for schizophrenia, but sometimes the results were inconsistent. Electronic search was carried out in November 2015. PubMed and Scopus databases have been used to find studies to introduce in this review. Only randomized-placebo-controlled add-on trials were taken into account. In this way, six articles were obtained for the discussion. Celecoxib showed beneficial effects mostly in early stages of schizophrenia. In chronic schizophrenia, the data are controversial, possibly in part for methodological reasons.